Impactos e desafios da implantação da norma de desempenho NBR 15.575/2013 em empresas construtoras de edificações multifamiliares - Karla Grasielle de Souza Belém (2018)
The search for the quality of products and services has been gaining space in the construction sector, which demands from companies a competitive position based on the reality of the market. This search was stimulated by the publication of the performance standard ABNT NBR 15.575 / 2013, which aims to guarantee to the users of the buildings the quality of the components and systems in operation of use by means of the fulfillment of normative requirements. Therefore, this work aims to analyze the challenges and impacts caused by the implementation of the mentioned standard in residential building construction companies in the cities of Montes Claros and Uberlândia (Minas Gerais, Brazil). For this, a bibliographic review was carried out, followed by case studies with the selected companies. As a source of evidence, we used semi-structured interviews with agents involved in the process of standardization, analysis of internal documents of each company surveyed and direct observation of work routines. The results indicate that sporadic training by professionals in the industry, insufficient data that prove the adequacy of items used in construction and professional culture are mostly responsible for difficulties in the face of the subject. This research indicates changes in design practices in construction companies and for agents involved in the normative process of residential buildings, which can help solve problems or improve work processes. For the Academy the present work brings contributions to the disciplines in which it is inserted. The intention is to contribute important and relevant information about the actions that impact professionals involved in the chain and in the construction sector when it comes to the implementation of the performance standard